Values education in a South African geography classroom - Sadie, Stephen (My University, 2014)
This study involves researching the key factors in the development of value and attitudes on grade 11 geography learners at Sacred Heart College. This required the design and teaching of three units on the themes of • Informal Settlement • Water Access and Conservation • Coal Mine at the Vaal River The research methodology is based on action research and complemented by the constant comparative method. This research is a case study in which the teacher is a participant observer in the process. The research is designed to move beyond other studies on values education in geography, which continue to highlight the need for values education and justify its purpose. This study proceeds fiom the assumption that values education is necessary but instead, seeks to understand the dynamics and factors involved in bringing about a change in the values and attitudes of the learners. In this sense, the study is a case study o f a small group o f learners to try and understand the intricate factors, which allow values education to occur. The study also critiques the lack of South African examples of values education in local textbooks and proceeds to design and implement three units o f South African value-laden lessons. This study gives impetus to OBE in South Africa, which has an important emphasis on values and attitudes. The study is also located in the context of Sacred Heart College, a school well known for its multicultural character and innovative curriculum programmes. The study investigates the factors which, either advance or inhibit values education such as teaching strategies, contextualisation, multiculturalism, the role of the teacher, politics, group work, action and learning support materials,